Positioning Madrasah dalam Penguatan Pendidikan Karakter - Fery Diantoro (Al-Hayat: Journal of Islamic Education, 2018)
Character education is one solution to the problems of morality, character and other deviant behavior that is happening in this country. Strengthening character education becomes something important that must be supported by all components ranging from educational institutions, families and communities. In order to support the reinforcement, the president also issued a regulation on strengthening character education. Madrasah that become one of the formal educational institutions are also required to carry out the strengthening of character education as mandated. The positioning of madrasah should also be appropriate in the organization of strengthening character education, as it will impact on community appraisal. Positioning madrasah in organizing character education reinforcement is carried out through intra-curricular, ko-curriculer and extracurricular programs and positioning madrasah in addressing school admission days, madrasah can take the five day entry option with a system integrating the madrasah system with the pesantren system or taking six day entry options by strengthening the three curricular programs , with programs that show off that can be directly seen and felt the benefits by the community.Pendidikan karakter menjadi salah satu solusi atas permasalahan moral, akhlak dan perilaku menyimpang lainnya yang sedang terjadi di Negara ini. Penguatan pendidikan karakter menjadi sesuatu yang penting yang mesti didukung oleh seluruh komponen mulai dari lembaga pendidikan, keluarga dan masyarakat. Dalam rangka mendukung penguatan tersebut presiden juga mengeluarkan Peraturan tentang penguatan pendidikan karakter. Madrasah yang menjadi salah satu lembaga pendidikan formal dituntut juga mampu melaksanakan penguatan pendidikan karakter sebagaimana yang telah diamanatkan. Positioning madrasah juga harus tepat dalam penyelenggaraan penguatan pendidikan karakter, karena akan berdampak pada penilaian masyarakat. Positioning madrasah dalam menyelenggarakan penguatan pendidikan karakter dilakukan melalui program intrakurikuler, kokurikuler dan ekstrakurikuler dan positioning madrasah dalam menyikapi hari masuk sekolah, madrasah dapat mengambil opsi hari masuk lima dengan sitem mengintegrasikan sistem madrasah dengan sistem pesantren atau mengambil opsi masuk enam dengan penguatan di ketiga program kurikuler, dengan program-program yang show off yang bisa langsung dilihat dan dirasakan manfaatnya oleh masyarakat.